Pengaruh Transformasi Digital dan Manajemen Perubahan Terhadap Kinerja Penyidik Ditreskrimum Polda Bali dalam Penerapan Aplikasi Elektronik Management Penyidikan (E-MP) - Amir, Mohammad; Earlyanti, Novi Indah; Prisgunanto, Ilham (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the influence of digital transformation and change management on the performance of investigators at the Ditreskrimum Polda Bali in implementing the Electronic Investigation Management (E-MP) application. The research focuses on understanding the extent to which these factors affect investigative effectiveness and identifying key drivers of investigator performance improvement in a digital system. A quantitative approach was employed using a survey method. Data were collected from 128 investigators at Ditreskrimum Polda Bali through questionnaires and analyzed using multinomial logistic regression. The analysis included the Likelihood Ratio Test, Wald Test, and Pseudo R-Square to assess model significance and explanatory power. Principal Component Analysis (PCA) was applied to address multicollinearity and enhance regression model stability. The findings indicate that digital transformation and change management significantly influence investigator performance. The Nagelkerke R-Square value of 0.866 suggests that the model explains 86.6% of variability in investigator performance. Furthermore, the Likelihood Ratio Test results confirm that predictor variables have a significant impact on the dependent variable with a p-value < 0.05. the regression equation is as follows ln(P(Y=0)P(Y=1))=β0+β1X1+β2X2. In conclusion, effective implementation of digital transformation and change management positively contributes to improved investigator performance in the use of E-MP. Therefore, enhancing digital technology training and strengthening change management strategies are highly recommended to optimize the utilization of E-MP in investigative environments.